2017
DOI: 10.1097/md.0000000000006690
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome in a postpartum hemorrhagic woman without hypertension

Abstract: Rationale:Posterior reversible encephalopathy syndrome (PRES), which diagnosis is based on clinical symptoms and radiological features, is a neurotoxic disease characterized by a set of clinical manifestations, such as seizure, headache, visual, and/or consciousness disturbance. It is the first case of PRES followed by postpartum hemorrhage (PPH) without underlying disease.Patient concerns:A 37-year-old healthy woman had PPH after caesarean section. Six days after delivery, headache occurred suddenly, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Previous observational studies showed that blood transfusion in the critically ill may have a deleterious effect on clinical outcomes, independent of illness severity or hemoglobin level [56,57]. Blood transfusion may induce not only circulatory overload, acute lung injury, and allergic reaction but also thromboembolism and stroke [5]. Peripartum transfusion increased the incidence of stroke more than 10-fold, although women who needed transfusions may also be at high risk for other stroke factors such as preeclampsia and PPH [58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies showed that blood transfusion in the critically ill may have a deleterious effect on clinical outcomes, independent of illness severity or hemoglobin level [56,57]. Blood transfusion may induce not only circulatory overload, acute lung injury, and allergic reaction but also thromboembolism and stroke [5]. Peripartum transfusion increased the incidence of stroke more than 10-fold, although women who needed transfusions may also be at high risk for other stroke factors such as preeclampsia and PPH [58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies showed that blood transfusion in the critically ill may have a deleterious effect on clinical outcomes, independent of illness severity or hemoglobin level [56,57]. Blood transfusion may induce not only circulatory overload, acute lung injury, and allergic reaction but also thromboembolism and stroke [5]. Peripartum transfusion increased the incidence of stroke more than 10-fold, although women who needed transfusions may also be at high risk for other stroke factors such as preeclampsia and PPH Readers should be aware of the limitations in the present study.…”
Section: Separately Inmentioning
confidence: 99%
“…Dysfunction of vascular endothelium triggers capillary leakage and disruption of the blood brain barrier ending with vasogenic edema. 7 Due to blood pressure fluctuation, arteriolar constriction and dilatation alter cerebral autoregulation. 7 This situation may cause breakdown of the blood brain barrier allowing extravasation of fluid into the brain parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to blood pressure fluctuation, arteriolar constriction and dilatation alter cerebral autoregulation. 7 This situation may cause breakdown of the blood brain barrier allowing extravasation of fluid into the brain parenchyma. On the other hand, focal vasoconstriction leads to local hypoperfusion, cyctotoxic edema and cerebral infarction resulting in vasogenic edema.…”
Section: Introductionmentioning
confidence: 99%